The measure of the West : a representation of travel - Siza, Álvaro, 1933-; Chiaramonte, Giovanni, 1948-2023; Cremascoli, Roberto; Zardini, Mirko (McGill-Queen's University Press, 2018)
"In 1984, Giovanni Chiaramonte photographed Álvaro Siza's building in Berlin, on whose façade some young people had written Bonjour Tristesse. The image was published on the cover of the magazine Lotus International. The following year, Siza and Chiaramonte met in Évora, on the occasion of a new series by the Italian photographer featuring the buildings of the great Portuguese architect. It marked the beginning of a long friendship and a shared reflection on architecture, photography, and urban life."-- Provided by publisher.
Manuscript originally written in Italian and originally published in Portuguese under title: A medida do ocidente: viagem na representação.
Keywords: Siza, Álvaro, -- 1933- -- Travel.; Chiaramonte, Giovanni, -- 1948-2023 -- Travel.; Chiaramonte, Giovanni, -- 1948-; Siza, Álvaro, -- 1933-; Cities and towns in art.; Cities and towns -- Pictorial works.; Art and architecture.; Architectural photography.; Art et architecture.; Photographie d'architecture.; ARCHITECTURE -- Adaptive Reuse & Renovation.; ARCHITECTURE -- Buildings -- Landmarks & Monuments.; ARCHITECTURE -- Professional Practice.; ARCHITECTURE -- Reference.; ARCHITECTURE -- General.; Architectural photography; Art and architecture; Cities and towns; Cities and towns in art; Travel; Electronic books.; Pictorial works